Use of Recycled Aggregates in Lime Mortars for Conservation of Historical Buildings - Menard Kilumile; Marilda Barra; Fatma Mohamed; Diego Aponte (Construction Materials, 2025)
The use of recycled burnt clay brick sand (RBS) and recycled concrete sand (RCS) in historical lime-based repair mortars can reduce the environmental impact caused by construction and demolition waste disposal. This study examined the use of fine recycled concrete and recycled brick aggregates for the production of historical repair mortars using hydraulic lime binder and the influence of the resulting mortars on the performance of historical buildings in reduced scale walls (stacks). Natural-river-sand mortar (NSM) was used as control. Results showed that the recycled-burnt-brick-sand mortar (RBSM) performed better in terms of strength compared to the recycled-concrete sand (RCSM) and the NSM mortars. At the age of 7 and 28 days, the flexural strength of the RBSM and the RCSM was 131% and 44%, respectively, and 300% and 68% above that of the control mortar. The 45-day flexural strength of the NSM and RCSM was similar whilst the RBSM mortar’s strength was 177% higher. The compressive strength followed similar trend. On the other hand, the strength and modulus of elasticity of the stacks were found to be largely influenced by the strength of the brick units.